2022
DOI: 10.1111/jcpp.13610
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal mental health mediates the effects of pandemic‐related stressors on adolescent psychopathology during COVID‐19

Abstract: BackgroundThis study examined whether COVID‐19‐related maternal mental health changes contributed to changes in adolescent psychopathology.MethodsA community sample of 226 adolescents (12 years old before COVID‐19) and their mothers were asked to complete COVID‐19 surveys early in the pandemic (April–May 2020, adolescents 14 years) and approximately 6 months later (November 2020–January 2021). Surveys assessed pandemic‐related stressors (health, financial, social, school, environment) and mental health.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…More pandemic-time parental mental health symptoms were associated with increased financial concerns during the pandemic in parents of autistic adolescents; this relationship was replicated in the pre-adolescent cohort but only at the bivariate level when other factors weren’t controlled for. This finding is in line with the previous literature that demonstrated the impact of the pandemic on parents ( Lengua et al, 2022 ; Yılmaz et al, 2021 ). Such impacts are expected given the substantial pressure social restrictions have placed on parents to deliver home-schooling and balance work demands, along with additional physical health, mental health and financial concerns.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More pandemic-time parental mental health symptoms were associated with increased financial concerns during the pandemic in parents of autistic adolescents; this relationship was replicated in the pre-adolescent cohort but only at the bivariate level when other factors weren’t controlled for. This finding is in line with the previous literature that demonstrated the impact of the pandemic on parents ( Lengua et al, 2022 ; Yılmaz et al, 2021 ). Such impacts are expected given the substantial pressure social restrictions have placed on parents to deliver home-schooling and balance work demands, along with additional physical health, mental health and financial concerns.…”
Section: Discussionsupporting
confidence: 93%
“…Risk factors for more parental mental health symptoms during the pandemic have included lower pre-pandemic family income and more pandemic-related stressors (e.g. loss of occupation) ( Lengua et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress and anxiety in parents, as well as exposure to increased information regarding the pandemic, may cause uncertainty, fear, and other psychological and social consequences for children (Fiorillo and Gorwood, 2020). A study of a community-based sample of mothers and children found that pandemic-related stressors led to an increase in maternal mental health symptoms, which then predicted greater psychopathology symptoms among adolescents (Lengua et al, 2022). Moreover, COVID-19-related threat information from parents and the community contributed to greater fear in children, particularly for younger children (Uy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we consider how the crisis in child and parent mental health are inextricably linked, through family processes. As hypothesized by the COVID-19 family disruption model (Prime et al, 2020), psychological distress, parenting stress, and economic pressure have weighed heavily on parents, leading to strain within family relationships, reductions in family cohesion, and threats to child mental health and well-being (Fosco et al, 2022; Lengua et al, 2022). Recognizing that pandemic-related family stress is a bidirectional and reciprocal process is essential to understanding the reverberations of the pandemic across time; stress in one family member or relationship may lead to stress in another family member or relationship, which in turn feeds back in a self-maintaining loop (Browne et al, 2021).…”
Section: What Is Next?mentioning
confidence: 99%